PENGEMBANGAN POTENSI PRODUK LOKAL SEBAGAI UPAYA PEMBANGUNAN PARIWISATA YANG BERBASIS MASYARAKAT - Indra Wahyudi; Aliah Rahman; Emy Ollong; Sylvia Irene Persulessy (Politeknik Negeri Ambon, 2023)
Maluku as an archipelagic province has natural beauty that can be utilized to improve the economy and welfare of the Maluku people. With the characteristics of beautiful islands, strong culture and local wisdom of the population, if maximized for the use of business opportunities, it is business development in the tourism sector. Blue economy is a new idea in development that is oriented towards the marine sector. The country of Morella is located along the coast with varying heights above sea level. The condition of the village which is located on the clean coast makes the country of Morella has many coastal tourist locations that are often visited by tourists, both local, national and foreign tourists. Besides being cheap, beach tourism is famous for its underwater beauty, which is the best diving and snorkeling spot. The problem that exists in the coastal tourist locations of Morella Village is that they have inadequate infrastructure so that it affects tourist attractions. In addition, there are no sales of local products as souvenirs typical of the country of Morella. The purpose of this research is to improve the community's economy by developing knowledge and skills of human resources in the production and marketing process, to improve the welfare of the community. The solution offered is to make a draft policy which is submitted to the Village/State party for further making a State Regulation that is made together with the Village Saniri.